Analysis of a Safe and Fasttrack L Prakash (LPR) Method of Reduction for Anterior Shoulder Dislocation - V. Kishore; A. K. Rajesh Babu; D. Venkatesh (Journal of Orthopedics, Traumatology and Rehabilitation)
Introduction: Anterior dislocation was the most common type of shoulder dislocation often encountered in emergencies. Many methods were described by authors for reduction, which involves either traction or sedation or some assistance, but they were not without iatrogenic complications. A universally acceptable and ideal method is not yet concluded. Dr L. Praksh (LPR) introduced a new method for reduction which is quick, safe, painless and does not require traction or sedation or assistance and without any complications. This study aims to analyze and safety of the LPR technique. Materials and Methods: This was a prospective study conducted in two different institutes by the same author and team. All the cases of acute anterior shoulder dislocation and dislocation with associated greater tuberosity fractures were diagnosed, and necessary details were recorded and reduced by the LPR method. A maximum of two attempts were tried on difficult patients. No traction, no sedation, and no assistance were followed during the maneuver. Time taken for reduction, complications if any were recorded. Results: Among 64 patients included in the study, 48 (75%) were male, 16 (25%) were female. The mean age was 37.5 (range 17–65) years. Associated greater tuberosity fractures were seen in 8 (12.5%) patients. LPR method successfully reduced shoulder dislocation in 63 (98.4%) patients, among them 2 (3%) reduced in second attempt. The average time taken for reduction was 3–4 min. No complications were recorded. Conclusion: L. Prakash (LPR) method of reduction for anterior dislocation of the shoulder is a FastTrack method which is safe, effective, near ideal and without complications even in associated greater tuberosity fractures.